Lipid Abnormalities in Patients with Type 2 Diabetes - Muhammad Khurram , Haris Gul , Fazal-Ur-Rahman , Hamama Tul Bushra Khar , Muhammad Faheem (Journal of Rawalpindi Medical College, 2013)
Background: To note association of glycemic control with lipid profile abnormalities in patients with type 2 diabetes mellitus (T2DM). Methods: In this cross sectional fasting blood samples of 226 T2DM were collected for glycosylated haemoglobin (HbA1c) and lipid profile. Association between glycemic control and lipid profile abnormalities were sought employing Chi2 or t test. Results: Mean patient age was 58.70±7.725 years. Majority (54%) patients were female. Mean HbA1C level was 9.6±2.06. Majority (81.4%) had poorly controlled diabetes. Dyslipidemia was noted in 80.1%. Significant association was noted between poor glycemic control and dyslipidemia (p <0.05). Conclusion: Poor glycemic control is common in our type II DM patients. Significant association exists between glycemic control and presence or absence of dyslipidemia.